Immune Evasion Mechanism and AXL - Son, Hye-Youn; Jeong, Hwan-Kyu (Frontiers in Oncology, 2021)
Extensive interest in cancer immunotherapy is reported according to the clinical importance of CTLA-4, and (PD-1/PD-L1) (programmed death (PD) and programmed death ligand (PD-L1)) in immune checkpoint therapies. AXL is a receptor tyrosine kinase expressed in different types of cancer and also in relation to resistance against various anti-cancer therapeutics as a result of poor clinical prognosis. AXL and its ligand, i.e., growth arrest-specific 6 (Gas6) proteins, are expressed on many cancer cells. The Gas6/AXL pathway is reported to promote cancer cell proliferation, survival, migration, invasion, angiogenesis, and immune evasion. AXL is an attractive and novel therapeutic target for impairing tumor progression from immune cell contracts in the tumor microenvironment. The GAS6/AXL pathway is of interest immunologically because it targets less antitumor immune responses. Additionally, several targeted therapies are selective and nonselective for AXL, which are in preclinical and clinical development in multiple cancer types. Overcoming the AXL pathway in immune evasion is important. Therefore, this review focuses on the role of the Gas6/AXL signaling pathway in triggering the immunosuppressive tumor microenvironment as immune evasion by regulating its composition and activating T-cell exclusion. It is also considered one of the hallmarks of cancer survival. Finally, this article discusses the activation of the Gas6/AXL signaling pathway, such as GAS6 and AXL expression levels in the tumor microenvironment, Gas6/AXL-mediated tumor immune evasion, and the function of Gas6/AXL pathway in tumor-specific immunity, especially PD-1/PDL-1 signaling. Additionally, Axl contributes to immune evasion in several ways with respect to regulatory T cells, natural killer (NK) cells with IL-15, apoptosis, and innate immune responses.